2003
DOI: 10.1034/j.1600-0609.2003.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of the human MRP1 and MRP2 mRNA expression in FACS‐sorted peripheral blood CD4+, CD8+, CD19+, and CD56+cells

Abstract: On an mRNA level both MRP1 and MRP2 were expressed in peripheral blood cells, with more than sevenfold higher MRP1 expression in all cell populations investigated. The impact of the MRP1 and MRP2 transcription in these cells remains to study. The use of beta2-microglobulin as a housekeeping gene could have a critical impact on the interpretation of RT-PCR data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…The demonstrated device efficiency is similar or better than those reported elsewhere for microfluidic-based systems [10,23]. We did not segregate the T lymphocytes collected from whole blood by sub-types to get a ratio metric measurement of T-lymphocyte sub-types, as reported by other groups and would likely be more challenging but could be done using a multiplexed magnetic bead assay [4,15]. Another recent report by Briggs et al explored the linearity and reproducibility of the measurements [10].…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The demonstrated device efficiency is similar or better than those reported elsewhere for microfluidic-based systems [10,23]. We did not segregate the T lymphocytes collected from whole blood by sub-types to get a ratio metric measurement of T-lymphocyte sub-types, as reported by other groups and would likely be more challenging but could be done using a multiplexed magnetic bead assay [4,15]. Another recent report by Briggs et al explored the linearity and reproducibility of the measurements [10].…”
Section: Resultsmentioning
confidence: 87%
“…Due to the lack of access to modern laboratory facilities having FACS machines, physicians in developing nations sometimes make their diagnosis and treatment evaluations without knowledge of the CD4+ T lymphocyte cell count in the patient's blood. The cost and maintenance of FACS machines make the technology expensive for medical centers and hospitals in developing nations [13][14][15][16]. For this reason, treatment options are often not customized to the patients even though it is known that the CD4+ T lymphocytes are highly variable between patients infected with HIV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used β2M because it has no pseudogene and the use of β2M as a housekeeping gene has a critical impact on the interpretation of PCR data. 32 In our assay, the dynamic quantification range (from 6 x 10 5 copies to 6 x 10 10 copies) was satisfactory for clinical use. When this system was applied to clinical samples, we found that there was a statistically significant increase (p < 0.01) in the average MRP1 expression level at the time of nonresponse or early relapse, compared with patients in remission.…”
mentioning
confidence: 88%